Mythological Themes in Artworks of Ernests Brastins and Arvids Brastins - Celmiņa-Ķeirāne, Austra (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
The aim of the study is to analyse artwork of Ernests Brastins (1892-1942) and Arvids Brastins (1893-1984) from the point of view of content and iconology, and the formal structure of work, which helps to reveal the author’s ideological direction. Using the comparative method, the visual text (artwork) is compared to the verbal (folklore) text, in an attempt to find parallels to the way they reflect Latvian mythological conceptions. An appropriate folksongs and beliefs are chosen for the artwork selected for the analysis, which serve as an explanatory material for the subject. The elements included in the work compositions are analyzed in the context of Latvian symbolic representations of natural phenomenon, godheads of pagan religion of pre-Christianity and ethical values.